Effects of 1-Methylcyclopropene to Atemoya Fruits (Annona atemoya Hort. cv. Petchpakchong) Postharvest Quality - ล้านไชย, มยุรา; สาตร์เพ็ชร์ , จิตตา; ศรีวิลัยวรรณ, โสภิดา; บุศราคำ, คนึงนิจ; เตชะศีลพิทักษ์, ธัญญะ; บุญกลาง, ธวัชชัย (Thai Journal of Science and Technology, 2021)
Petchpakchong sugar apple (Annona atemoya Hort. cv. Petchpakchong) is a favorable tropical fruit due to its flavor, luscious-odor and taste, and fewer seeds, albeit its short shelf life which is according to rapid physiological changes. In this study, 1-MCP was applied to petchpakchong sugar apples, which were harvested after flowering 110-120 days, for shelf life-prolonging. The sugar apples were fumigated in a range concentration of 1-MCP including 0, 1,000, 2,000, and 4,000 ppb, prior kept at 25±2 o C and 70±5 %RH. The results presented that 1-MCP could be enhanced and prolong the shelf life of petchpakchong sugar apple without abnormal symptoms. The Fruit qualities at 2,000 ppb of 1-MCP were the most accepted by the consumer. However, peel color changes, weight loss, total soluble solids, titration acidity, respiratory rate, and ethylene production were congruence-increased to the fruit’s maturity.